How do mothers nurture love via parenting? - Jamiah Manap,; Fazilah Idris,; Syaidatun Nazirah Abu Zahrin,; Zuraidah Ali, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Love and compassion are two of the most persuasive emotional attachments in the family. Mothers’ true love empowers children’s survival in the world and hereafter. Thus, this research aims to understand on how the Malaysian award winners for exemplary mothers category (Ibu Mithālī) show their love and mercy to their children in order to develop parent-child attachment. To answer the research question, research was done using Grounded Theory approach. As a result, three main themes have emerged: physical touch, emotional touch and spiritual touch. Love and mercy from mothers are pertinent in child development. Therefore, mothers should nurture their children with love and compassion to balance firm discipline and strict rules in the family.